2017
DOI: 10.1002/ca.23035
|View full text |Cite
|
Sign up to set email alerts
|

Pictorial essay of ultrasound‐reconstructed coronal plane images of the uterus in different uterine pathologies

Abstract: Imaging in the major planes (horizontal, coronal, and sagittal) of the uterus is important for determining anatomy and allowing the findings to be standardized, and for evaluating and diagnosing different pathological conditions in clinical practice. Examination of the coronal plane is an important step in identifying uterine pathologies and their relationships to the endometrial canal. Three-dimensional (3D) ultrasound reveals the normal anatomy better and improves the depiction of abnormal anatomy, as the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…However, the gold standard for diagnosing endometriosis is laparoscopy with biopsy to demonstrate the histological presence of the endometrial tissues [ 6 , 37 ]. Chocolate cysts can be visualized via ultrasonography, and DIE can be detected using transvaginal ultrasound [ 6 , 39 ]. Pelvic magnetic resonance imaging (MRI) has been touted as a better imaging modality in patients with deep infiltrating pelvic endometriosis, as it offers high-resolution images with excellent tissue characterization [ 9 , 17 ].…”
Section: Reviewmentioning
confidence: 99%
“…However, the gold standard for diagnosing endometriosis is laparoscopy with biopsy to demonstrate the histological presence of the endometrial tissues [ 6 , 37 ]. Chocolate cysts can be visualized via ultrasonography, and DIE can be detected using transvaginal ultrasound [ 6 , 39 ]. Pelvic magnetic resonance imaging (MRI) has been touted as a better imaging modality in patients with deep infiltrating pelvic endometriosis, as it offers high-resolution images with excellent tissue characterization [ 9 , 17 ].…”
Section: Reviewmentioning
confidence: 99%
“…According to this classification, it is possible to distinguish types of isthmocele based on the shape: triangle (Figure 1A), semicircle (Figure 1B), rectangle (Figure 1C), circle (Figure 1D), droplet (Figure 1E) and inclusion cyst (Figure 1F) [65,104]. Other important parameters to evaluate for a correct assessment of the isthmocele are: Residual myometrial thickness (RMT), isthmocele depth (DI), isthmocele width (WI), cervical thickness (CT), distance from the fundus to isthmocele (DFUI) and distance from the isthmocele to the cervix (DCI) [105,106].…”
Section: Transvaginal Ultrasound Examinationmentioning
confidence: 99%
“…One study revealed that the accuracy of MRI in diagnosing adenomyosis increases when the mean junctional zone is thicker than 12 mm (Reinhold et al, ). In addition, 3D ultrasound clearly demonstrates the thickened endomyometrial junction and the hyperechoic regions caused by the endometrial tissue (Grigore et al, ).…”
Section: Adenomyosismentioning
confidence: 99%
“…A study assessing the reliability of the FIGO classification revealed that only 14% of the fibroids had a single uniform classification among the evaluating physicians, while 48% had two different classifications and others had three or more classifications (Laughlin‐Tommaso et al, ). The use of a 3D ultrasound is more accurate in differentiating the location and depth of invasion than with a 2D ultrasound, as it provides better patient management (Grigore et al, )…”
Section: Uterine Leiomyomasmentioning
confidence: 99%